Permainan Ular Tangga Berbasis Game Based Learning untuk Meningkatkan Berpikir Kritis Siswa pada Pelajaran IPA - Agus Aini Purnama; Muhammad Kalkautsar (Departement of Mathematics Education, 2023)
Game Based Learning Snakes and Ladders Game to Improve Critical Thinking. This study aims to (1) produce Game Based Learning (PBL) learning media for snakes and ladders to improve critical thinking skills and (2) determine the effectiveness of snakes and ladders learning media based on GBL in improving the critical thinking skills of sixth grade elementary school students. This study uses the Borg and Gall research design. The operational field test subjects consisted of 30 students of grade six (V) SD IT ZUTSAQIF and SD IT ZUTSAQIF; each for the experimental and control classes. The research findings are as follows. (1) GBL-based monopoly game learning media according to student needs. According to material experts and educational media experts, the learning media for snakes and ladders games developed based on GBL are in the